Undescribed Meroterpenoids from Hypericum japonicum with Neuroprotective Effects on H2O2 Insult SH‐SY5Y Cells Targeting Keap1‐Nrf2. Issue 11 (15th March 2022) - Hu, Linzhen; Wang, Zhenzhen; Tong, Zhou; Hu, Ping; Kong, Luqi; Luo, Mengying; Li, Xiao‐Nian; Zhang, Yuexing; Huang, Zhiyong; Zhang, Yonghui
Comprehensive Summary: Unreported tautomeric/enantiomeric meroterpenoids, (±)‐hyperjaponols I—K (1—3), were discovered from Hypericum japonicum . Comprehensive chemical investigations established the absolute characteristics of these stereoisomers. The TS calculation demonstrated that 1a and 2a easily occur enol‐keto tautomerism with steady configurations individually. Amongst isolates, 1b showed the strongest neuroprotective activity with the concentration at 25 μmol/L on H2 O2 insult SH‐SY5Y cells. In vitro molecular biological experiments manifested that 1b activated the Keap1‐Nrf2‐ARE pathway, leading to the promotion of Nrf2 nuclear translocation, downregulation of the expression level of Keap1, and upregulation of the levels of Nrf2, NQO‐1, and HO‐1. The results of in silico simulation showed that 1b possessed good binding features with Keap1 (5FNQ) via forming multiple typical hydrogen and hydrophobic bonds as well as less fluctuation of RMSD and RMSF during a natural physiological condition. Abstract :